Variation in mycorrhizal associations with tulasnelloid fungi among populations of five Dactylorhiza species. - Hans Jacquemyn; Agnieszka Deja; Koen De hert; Bruno Cachapa Bailarote; Bart Lievens (PLoS ONE)
Background Orchid species rely on mycorrhizal symbioses with fungi to complete their life cycle. Although there is mounting evidence that orchids can associate with several fungi from different clades or families, less is known about the actual geographic distribution of these fungi and how they are distributed across different orchid species within a genus. Methodology/principal findings We investigated among-population variation in mycorrhizal associations in five species of the genus Dactylorhiza (D. fuchsii, D. incarnata, D. maculata, D. majalis and D. praetermissa) using culture-independent detection and identification techniques enabling simultaneous detection of multiple fungi in a single individual. Mycorrhizal specificity, determined as the number of fungal operational taxonomic units (OTUs), and phylogenetic diversity of fungi were compared between species, whereas discriminant analysis was used to compare mycorrhizal spectra across populations and species. Based on a 95% cut-off value in internal transcribed spacer (ITS) sequence similarity, a total of ten OTUs was identified belonging to three different clades within the Tulasnellaceae. Most OTUs were found in two or more Dactylorhiza species, and some of them were common and widespread, occurring in more than 50% of all sampled populations. Each orchid species associated with at least five different OTUs, whereas most individuals also associated with two or more fungal OTUs at the same time. Phylogenetic diversity, corrected for species richness, was not significantly different between species, confirming the generality of the observed orchid mycorrhizal associations. Conclusions/significance We found that the investigated species of the genus Dactylorhiza associated with a wide range of fungal OTUs from the Tulasnellaceae, some of which were widespread and common. These findings challenge the idea that orchid rarity is related to mycorrhizal specificity and fungal distribution.